International cooperation : the extents and limits of multilateralism - Touval, Saadia; Zartman, I. William (Cambridge University Press, 2010)
A number of new approaches to the subject of international cooperation were developed in the 1980s. As a result, further questions have arisen, particularly with regard to the methods and limits of cooperation and the relationship between cooperation and the debate over multilateralism. International Cooperation considers these questions, identifies further areas for research, and pushes the analysis of this fundamental concept in international relations in new directions. Its two parts address the historic roots and modern development of the notion of cooperation, and the strategies used to achieve it, with a conclusion that reaches beyond international relations into new disciplinary avenues. This edited collection incorporates historical research, social and economic analysis and political and evolutionary game theory.--From publisher description.